ANALISIS KINERJA KEUANGAN BMT (KSPPS) (Studi Kasus BMT Pratama Cahaya Mentari Rawalumbu Kota Bekasi) - WAHIDIN MUSTA’IN BILLAH (DIRHAM Jurnal Ekonomi Islam, 2021)
The purpose of this research is to improve the financial performance of Baitul Maal wat Tamwil (BMT) Pratama Cahaya Mentari Rawalumbu Kota Bekasi using SWOT analysis. In this study, using primary and secondary data obtained from financial reports. The research method used is a descriptive qualitative method. Based on the ministerial regulation, regarding the cooperative with achievements, it can be concluded that performance and financial management at BMT based on the results of the data are considered to have been running at 51%. This is due to the limited funds that can be used. In terms of cash flow, it is still minus because BMT KSPPS Pratama Cahaya Mentari has just been established, while there are fixed expenses that must be issued every month such as electricity and employee salaries. This is still assisted by the leadership of the Muhammadiyah Rawalumbu Branch.